An equation is shown below:
4(x − 3) − 5(x + 1) = 3
Which statement shows a correct next step in solving the equation? (1 point)
A: The equation can become 4x − 12 − 5x − 5 = 3 by applying the associative property of multiplication.
B: The equation can become 4x − 3 − 5x + 1 = 3 by applying the associative property of multiplication.
C: The equation can become 4x − 3 − 5x + 1 = 3 by applying the distributive property.
D: The equation can become 4x − 12 − 5x − 5 = 3 by applying the distributive property.